Utvärdering av miljöbonus IP-lantbruk - Boström, Patrik; Ekenstam, Carl af (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
The Dairy business is changing a lot because of some scandals in the agricultural area for example the BSE crises in Great Britain. Because of the scandals the food industry and the farm association have created a certifying system; IP-Sigill Swedish standard system.